Designing Accounting Software Using Microsoft Access For Cv C&L Ocean Ship - Dea Tiara Monalisa Butar-Butar; Juwenni Chia (Universitas Internasional Batam, 2024)
The deficient accounting recording system in CV C&L Ocean Ship is a result of manual transaction recording, causing inefficiencies and rendering financial reports irrelevant. This situation leads to potential inaccuracies and gaps in the completeness of reports crucial for decision-making. The objective of this community service initiative is to establish a Microsoft Access-based accounting system, encompassing forms, a bookkeeping system, and financial reporting. The methodology involves data collection through observations and partner interviews. The system includes three master lists there are main menu, transaction menu and report menu. The main menu has chart of account, inventory, supplier list, customer list, sales list, and employee list. Transaction menus have six forms to help owner record their daily transaction. The last one is the report menu contains nine types of financial reporting to assist the owner in knowing better about the company. These outputs are designed to assist Micro, Small, and Medium Enterprises (MSMEs), like CV C&L Ocean Ship, in gaining insights into inventory turnover and financial conditions beyond just cash flows. Consequently, MSMEs can enhance decision-making processes, boost sales, and better monitor their inventory.